2008
DOI: 10.1007/s11695-008-9443-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morbid Obesity on Chewing Ability

Abstract: The chewing parameters were affected in fully dentate patients with morbid obesity compared with controls, emphasizing the need for a systematic evaluation of both dental status and chewing ability in patients scheduled for bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 25 publications
(33 reference statements)
4
29
0
7
Order By: Relevance
“…Six of these articles support the argument that obese adults have fewer teeth compared to normal weight individuals 24,26,27,29,30,31 , however a case control study found no significant difference between the number of teeth in normal weight and obese individuals 23 . Two of the articles quote the significance of having less than 21 teeth which obesity.…”
Section: Reduced Number Of Teethmentioning
confidence: 86%
“…Six of these articles support the argument that obese adults have fewer teeth compared to normal weight individuals 24,26,27,29,30,31 , however a case control study found no significant difference between the number of teeth in normal weight and obese individuals 23 . Two of the articles quote the significance of having less than 21 teeth which obesity.…”
Section: Reduced Number Of Teethmentioning
confidence: 86%
“…Furthermore, many studies have established that problems in oral function are more frequent in elderly who have fewer than four FUs; they report difficulties in chewing or swallowing and they tend to avoid hard foods, including meat, vegetables and bread. They can consequently be at risk of malnutrition, which may affect their general health and reduce their life expectancy [30,34-37]. Previous studies have found significant associations between dental status (numbers of teeth, absence of dentures) and nutritional status among the elderly [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The mean chewing frequency is slowed down in subjects with chewing deficiencies while eating any type of resistant food. Previous studies on the chewing ability of dentally impaired subjects showed that a decrease in the number of functionally paired teeth and oral rehabilitation with removable dentures were linked to a decrease in CT and CC values and to an increased D50 value 9,14 . Nevertheless, the physiological impact of RPDM rehabilitation has been seldom studied.…”
Section: Introductionmentioning
confidence: 97%